Análise da paisagem para a identificação de fatores de pressão antrópica na zona de amortecimento da Estação Ecológica de Jataí, SP - Oliveira, Leandro José (2017)
The establishment of specially protected spaces is an excellent tool of environmental conservation against the various impacts caused by human activities on the environment. In Brazil the Law 9985/2000 instituted the National System of conservation units (SNUC) and as a result of this, several areas already segregated and others have created a legal protection for maintenance of their habitats. In the State of São Paulo stands out as the largest area of Cerrado protection Ecological station of Jataí (EEJ), however the unit is surrounded by powerful human, and enabled some of these are potentially harmful in order to provide pressure to the ecological balance on EEJ. The tools available to the Manager and his Board are not always effective to prevent the advance of disturbances in the buffer zone (ZA) for several factors, time, lack of resources, lack of staff, unavailability of constant monitoring by the protective forces of the State. In this scenario arises the concept of use of Remotely Piloted Aircraft (RPAS) for monitoring of these pressures. The initial goal of this research was to seek historical bases of conception of RPAS and the landmarks that involved its development, as well as meet and describe the main existing legislations in the world and in Brazil on the theme, being established that the employment of these aircraft is legally protected and such regulations tend to evolve along with technology, that the use is a one-way street and that human relationships are directly affected by this revolution. Out-performed spatialization of the attendances of occurrences in the ZA data made available by the environmental police with and identified several factors of anthropic pressure to EEJ (Flora, hunting, fishing, burned, and mining), moreover, considering the destructive potential of the illegal extractions of sand in the bounds of the river Mogi Guaçu out performed aerofotográfico using lifting RPAS and established the destruction from Mogi Guaçu River's ravine through mine activities After comparisons with previous images if you noticed the size of the destruction, in possession of the area hit was calculated the values in Brazilian reais and profit were found at the home of milhões reais. After the lifting of this data was drawn map with the vectors of pressure that afflict the conservation unit, as well as proposed actions to be adopted by the Manager in order to cool these forces and, in addition, proposed methodology for monitoring anthropogenic actions in areas of conservation units (CU), that in the present research proved efficient and low operating cost compared to currently available to managers of UC Yet such methodology merits further trials to prove its effectiveness.